The Role of Political Economy Analysis in Development Policy Operations - Independent Evaluation Group (World Bank, Washington, DC, 2017)
This learning product reviews the extent to which political economy analysis (PEA) is used to improve the design of development policy operations (DPOs) and how effective it has been. Although the World Bank’s mandate explicitly precludes it from engaging in politics, an understanding of the political economy is critical for the organization’s effectiveness. A political economy perspective broadens the World Bank’s operational considerations beyond technical analysis to the significance of power relations and the national political processes. This study mostly builds on evaluative findings from previous IEG work, including ICRRs, PPARs of long-term programmatic series (Tanzania, Vietnam, Uganda, and Ghana PRSCs). Supplementary evaluative evidence was gathered through a portfolio review of randomly selected DPOs, internal PEA reports, and Systematic Country Diagnostic reports (SCDs) relevant for DPOs. The study found that PEA can improve the design of DPOs by identifying implementation risks and mitigating action; there are different ways to make use of PEA; PEA can inform specific design elements, and that PEA can be used in self-evaluations to better analyze factors affecting program effectiveness and contribute to knowledge and improved design.